'K-Bot' Knowledge Enabled Personalized Healthcare Chatbot. Issue 1 (April 2021) - Pradhan, Rahul; Shukla, Jaya; Bansal, Mani
Abstract: In the present scenario when most of the things are just a click away, people consider visiting hospitals as the most effective, reliable, and convenient way for their routine check-ups or disease diagnosis. In the past few years, Machine Learning has been playing a major role in the domain of healthcare. The proposed system or approach focuses on creating an alternate using Decision Tree Algorithm where people can interact with chatbot and it will identify other symptoms and predict the disease along with the confidence level and thus recommending a specialized doctor. Using the above framework can help people save their time and money as well.